Nonlinear household earnings dynamics, self-insurance, and welfare - Mariacristina De Nardi; Giulio Fella; Gonzalo Paz Pardo (Queen Mary University of London, School of Economics and Finance, 2018)
Earnings dynamics are much richer than typically assumed in macro models with heterogeneous agents. This holds for individual-pre-tax and household-post-tax earnings and across administrative (Social Security Administration) and survey (Panel Study of Income Dynamics) data. We study the implications of two processes for household, post-tax earnings in a standard life-cycle model: a canonical earnings process (that includes a persistent and a transitory shock) and a rich earnings dynamics process (that allows for age-dependence of moments, non-normality, and nonlinearity in previous earnings and age). Allowing for richer earnings dynamics implies a substantially better profit of the evolution of cross-sectional consumption inequality over the life cycle and of the individual-level degree of consumption insurance against persistent earnings shocks. Richer earnings dynamics also imply lower welfare costs of earnings risk, but, as the canonical earnings process, do not generate enough concentration at the upper tail of the wealth distribution.
Keywords: D14; D31; E21; J31; 330; Earnings risk; savings; consumption; inequality; life cycle; Haushaltseinkommen; Privater Konsum; Optimale Besteuerung